Security in computing and communications : 5th International Symposium, SSCC 2017, Manipal, India, September 13-16, 2017, Proceedings /: 5th International Symposium, SSCC 2017, Manipal, India, September 13-16, 2017, Proceedings. (2017) - Unknown
No abstract available